Quantitative analysis of ocular deviation under eye occlusion: a descriptive study using the ORTe EYENAC eye-tracking system - Shunya Tatara; Yuna Magara; Touko Sasaki; Fumiatsu Maeda; Noriaki Murata; Kazuhiro Itagaki; Tomoya Handa; Haruo Toda (BMC Ophthalmology)
Abstract Background The cover–uncover test is traditionally used in the qualitative assessment of heterotropia and heterophoria, while the alternate prism cover test (APCT) quantifies ocular deviations. However, the APCT is time-consuming and prone to interexaminer variability. Video-oculography technology offers a promising alternative for quantifying ocular deviation under occlusion. This study aims to visualize ocular deviation during occlusion and determine the time it takes for deviation to stabilize in participants with exodeviation using the ORTe EYENAC eye-tracking system. Methods The study participants included 15 university students aged 20–22 years, among whom 13 had exophoria, 1 had intermittent exotropia, and 1 had exotropia. Eye position was measured using the ORTe EYENAC, which records gaze when one eye is occluded. Data were fitted to a logistic function to estimate ocular deviations, deviation speed, and stabilization time. The overshoot depth was defined as the maximum deviation beyond the final position before stabilization. Spearman’s rank correlation coefficient analyzed the correlations between the deviation angle, speed, and stabilization time. Results The fusion-free eye position stabilized at 3.33 ± 2.39 s among those with exophoria. Significant correlations were found between the deviation angle and deviation speed (rs = − 0.582, p = 0.0403), as well as between the deviation angle and stabilization time (rs = 0.663, p = 0.0135). An overshoot of > 1°, 0.5°–1.0°, and < 0.5° was seen in 3, 4, and 6 patients, respectively. The overshoot depth also correlated with deviation speed (rs = 0.775, p = 0.0029). Conclusions Ocular deviation under occlusion was effectively visualized in participants with exodeviation using the ORTe EYENAC, providing a clear representation of eye movement during the cover test. Among participants with exophoria, the fusion-free eye position stabilized at an average of 3.33 ± 2.39 s. However, the stabilization time varied with the angle of ocular deviation, suggesting that the occlusion time needs to be individually designed based on the angle of strabismus.